2011
DOI: 10.1257/app.3.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Peers, Neighborhoods, and Immigrant Student Achievement: Evidence from a Placement Policy

Abstract: We examine to what extent immigrant school performance is affected by the characteristics of the neighborhoods that they grow up in. We address this issue using a refugee placement policy that provides exogenous variation in the initial place of residence in Sweden. The main result is that school performance is increasing in the number of highly educated adults sharing the subject's ethnicity. A standard deviation increase in the fraction of high-educated in the assigned neighborhood raises compulsory school G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
74
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 33 publications
(38 reference statements)
7
74
0
Order By: Relevance
“…The policy has been carefully documented elsewhere and has been used to examine the impact of neighborhood conditions on refugees' socioeconomic outcomes (see e.g. Edin, Fredriksson and Åslund 2003;Fredriksson 2009, Åslund andRooth 2007;Åslund et al 2011). We refer to these studies for a more comprehensive treatment of the policy.…”
Section: Using the Settlement Policy To Identify The Effect Of Inequamentioning
confidence: 99%
See 2 more Smart Citations
“…The policy has been carefully documented elsewhere and has been used to examine the impact of neighborhood conditions on refugees' socioeconomic outcomes (see e.g. Edin, Fredriksson and Åslund 2003;Fredriksson 2009, Åslund andRooth 2007;Åslund et al 2011). We refer to these studies for a more comprehensive treatment of the policy.…”
Section: Using the Settlement Policy To Identify The Effect Of Inequamentioning
confidence: 99%
“…The policy has been used in several previous studies to investigate peer and neighborhood effects among refugees (see e.g. Edin, Fredriksson and Åslund 2003;Åslund and Fredriksson 2009;Åslund et al 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar way, a large literature has shown that differences in neighborhood quality (such as the level of income and ethnic segregation) contribute in explaining differences in educational outcomes (e.g. Chetty, Hendren and Katz 2015;Åslund, Edin, Fredriksson, and Grönqvist 2011;Grönqvist 2006;Grönqvist, Niknami and Robling 2015).…”
Section: Introductionmentioning
confidence: 89%
“…We exploit the fact that the -otherwise homogeneous-population 2 Other studies examine the eects of ethnic diversity on productivity at the country (Montalvo and Reynal-Querol, 2005), region (Ozgen et al, 2011a) or city level (Ottaviano and Peri, 2006;Lee and Nathan, 2011). Related are also studies measuring the impact of ethnic composition of schools or neighborhoods on educational outcomes (e.g., Hoxby, 2000;Angrist and Lang, 2004;Card and Rothstein, 2007;Hanushek et al, 2009;Aslund et al, 2011).…”
Section: Introductionmentioning
confidence: 99%